Multicomponent supervised tele-rehabilitation versus home-based self-rehabilitation management after anterior cruciate ligament reconstruction: a study protocol for a randomized controlled trial - Kexin Wang; Linbo Peng; Mingke You; Qian Deng; Jian Li (Journal of Orthopaedic Surgery and Research, 2024)
Abstract Introduction Our study aims to assess the effectiveness of multicomponent supervised tele-rehabilitation compared to home-based self-rehabilitation management in patients following anterior cruciate ligament reconstruction (ACLR). Methods The current study is designed as a single-center, single-blinded, randomized controlled, two-arm trial. Participants will be randomized and allocated at a 1:1 ratio into either a multicomponent supervised tele-rehabilitation group or a home-based self-rehabilitation group. All participants receive uniform preoperative education through the HJT software. Participants in the intervention group undergo multicomponent supervised tele-rehabilitation, while those in the control group follow a home-based self-rehabilitation program. All the participants were assessed and measured for the included outcomes at the outpatient clinic before the procedure, and in 2, 4, 8, 12, and 24 weeks after ACLR by two assessors. The primary outcome was the percentage of patients who achieve a satisfactory active ROM at the 12 weeks following the ACLR. The satisfactory active ROM was also collected at 2, 4, 8, and 24 weeks after ACLR. The secondary outcomes were active and passive range of motion (ROM), pain, muscle strength, and function results. Registration details Ethical approval has been obtained from the West China Hospital Ethics Committee (approval number 2023−1929, December 2023). The trial has been registered on ClinicalTrials.gov (registration number NCT06232824, January 2024).